Форми управління в органах прокуратури України - Рибалка, Н. О.; Rybalka, N. O. (Держава та регіони. Серія: Право. - 2013. - Вип. 2(40). - С. 53-57, 2013)
У статті проаналізовано поняття та види форм управління в органах прокуратури України. Акцентовано на особливостях, що притаманні правовим формам управління, організаційним формам, матеріально-технічному забезпеченню реалізації управління в органах прокуратури.

The analysis of the concept and types of forms of government in the prosecution. Attention is paid to features that are inherent legal forms management, organizational forms, logistics management forms in the prosecution. The purpose of this article is making teoretiko-methodological principles of improvement of legal forms of administrative activity in the organs of office of public prosecutor of Ukraine and with their account of development of suggestions in relation to subsequent development of the legal adjusting and practice of pravozastosuvannya in the organs of office of public prosecutor of Ukraine. Forms of management organs are offices of public prosecutor, predefined them by specific tasks and functions and that is why characterized own maintenance and have own essence signs. Vrakhovuyuchi the resulted opinions of research workers and specific of activity of organs of office of public prosecutor of Ukraine, for classification of management forms it follows a base criterion to choose the features of consequences, which arise up as a result of the use of certain form and degree of legal regulation of process of its application. By the forms of management in the organs of office of public prosecutor legal and organizational. Legal forms of management in the organs of office of public prosecutor, as a result of realization of jurisdiction of the authorized subject managements, maximally well-regulated the norms of legal acts and draw direct legal consequences, namely, set change, or abolish concrete legal relationships, create or bring in change to legal status of organs of office of public prosecutor, determine jurisdiction of pidkontrol'nikh objects of management.

В статье выполнен анализ понятия и видов форм управления в органах прокуратуры Украины. Акцентировано внимание на особенностях, присущих правовым формам управления, организационным формам, материально-техническому обеспечению реализации управления в органах прокуратуры.
Forms of governance in the prosecution of Ukraine
Формы управления в органах прокуратуры Украины
Keywords: органи прокуратури; форма державного управління; правові форми; організаційні форми; prosecution; form of government; legal forms; organizational forms; органы прокуратуры; форма государственного управления; правовые формы; организационные формы